## Solving the Equation (y-1)² = 9

This equation represents a simple quadratic equation. Let's break down how to solve it step-by-step.

### 1. Taking the Square Root

To get rid of the square, we take the square root of both sides of the equation:

√((y-1)²) = ±√9

This gives us:

y - 1 = ±3

### 2. Isolating 'y'

Now, we isolate 'y' by adding 1 to both sides:

y = 1 ± 3

### 3. Finding the Solutions

This gives us two possible solutions:

**y = 1 + 3 = 4****y = 1 - 3 = -2**

Therefore, the solutions to the equation (y-1)² = 9 are **y = 4** and **y = -2**.